Personalizing NSCLC therapy by characterizing tumors using TKI-PET and immuno-PET. (May 2017) - Bahce, I.; Yaqub, M.; Smit, E.F.; Lammertsma, A.A.; van Dongen, G.A.M.S.; Hendrikse, N.H.
Highlights: NSCLC immuno-PET enables imaging of mAb target expression. NSCLC TKI-PET shows tracer accumulation in high affinity tumors. Immuno-PET and TKI-PET show promise as imaging biomarkers for response prediction. Abstract: Non-small cell lung cancer (NSCLC) therapy has entered a rapidly advancing era of precision medicine with an ever increasing number of drugs directed against a variety of specific tumor targets. Amongst these new agents, tyrosine kinase inhibitors (TKIs) and monoclonal antibodies (mAbs) are most frequently used. However, as only a sensitive subgroup of patients benefits from targeting drugs, predictive biomarkers are needed. Positron emission tomography (PET) may offer such a biomarker for predicting therapy efficacy. Some of the TKIs and mAbs that are in clinical use can be radioactively labeled and used as tracers. PET can visualize and quantify tumor specific uptake of radiolabeled targeting drugs, allowing for characterization of their pharmacokinetic behavior. In this review, the clinical potential of PET using radiolabeled TKIs (TKI-PET) and mAbs (immuno-PET) in NSCLC is discussed, and an overview is provided of the most relevant preclinical and clinical studies.